(s-4)/3=2

Simple and best practice solution for (s-4)/3=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (s-4)/3=2 equation:



(s-4)/3=2
We move all terms to the left:
(s-4)/3-(2)=0
We multiply all the terms by the denominator
(s-4)-2*3=0
We add all the numbers together, and all the variables
(s-4)-6=0
We get rid of parentheses
s-4-6=0
We add all the numbers together, and all the variables
s-10=0
We move all terms containing s to the left, all other terms to the right
s=10

See similar equations:

| c-77=-40 | | 9a+6=3a+12 | | 4x−(12÷3)+2x=20 | | (2x-5)(7x-17)=85 | | 1=x/1+1 | | 5x-20=3x+30=2x+10 | | -26=2v+8-5v | | u-8.35=9.8 | | 2x-10+x+34+x=180 | | -26=2v+ | | 6x-35+1x+29+4x+11=192 | | 8j-4(j+8)=8 | | w/5+3=-3 | | 6+.50x=12+.25x | | 3(a-3)+6=30 | | 4(2x+1)=2(3x+1 | | 4x-5=3(3-x) | | 7=8+p/4 | | 2x25=30 | | -5+b2=-b | | 2x+10=3x+30=5x-20 | | –28=d/25 | | 75=6m+9 | | 5.4m-10=14 | | 28+y=51 | | 20p=500 | | 2(1-2x)=x-3= | | -6(2r+8)=10(r-3 | | −5x​ −12=30 | | 10-4n=70 | | -x+11+2x=7+3x+4 | | u+8/5=6 |

Equations solver categories